Differential effects of message framing on obesity policy support between democrats and republicans - Lee, Tae Kyoung (2020)
This study tests whether gain- and loss-framed messages about establishing obesity-reducing policies have different persuasive effects on Republicans and Democrats. In a randomized between-subject experiment, participants (N = 384) read a message emphasizing either benefits to a society by establishing policies aimed to reduce obesity (i.e., gain-framed message) or costs to a society that fails to establish those policies (i.e., loss-framed message). Results indicated that Democrats perceived the gain-framed message as more persuasive than the loss-framed message and the perceived argument strength fully mediated the framing effect on Democrats' policy support; however, there was no framing effect on perceived argument strength among Republicans. On the other hand, the gain-framed message led Republicans to attribute the cause of obesity less to the individual level compared to the loss-framed message and the no-message condition. We observed no framing difference among Democrats on causal attributions. Theoretical and practical implications of these findings are discussed.